Kultur Antera untuk Percepatan Perakitan Varietas Padi di Indonesia - Iswari S Dewi; Bambang S. Purwoko (Jurnal AgroBiogen, 2012)
Rice is a staplefood crop in Indonesia, while the need is increasing due tohigh rice consumption as well as population increase. Theproblems can be solved through increase of national riceproduction. Productivity of lowland and upland should beincreased intensively and other potential dry area outsideJava and Bali Islands should be considered for extending thearea of production. Recently, high yielding variety such assemi dwarf variety, hybrid rice, and new plant type of ricewere being developed by Indonesian breeders. However,new method is needed to complement conventionalbreeding method in order to accelerate rice breeding.Anther culture is one of in vitro culture techniques that canbe used to accelerate the obtainment of pure lines throughdoubled-haploids (DHs) regenerated at first generation ofculture for less than one year. Thus, application of antherculture in conventional breeding will increase the efficiencyof selection process as well as reducing the cost for labour,land and breeder’s time. The obtainment of green plantletsderived from anther culture of indica rice subspecies hasbeen improved by the addition of 1 mM putrescine intoinduction and regeneration media. Recently, several uplandrice lines tolerant to abiotic stresses (i.e. low light intensityand aluminum toxicity) and biotic stresses (i.e. leaf andneck blast), several lowland rice/paddy lines tolerant tobiotic stresses (i.e. bacterial leaf blight and blast), andseveral hybrid parental lines (i.e. male sterile, maintainerand restorer) were obtained in 2-3 years from several ricebreeding program involving anther culture. However,potential use anther culture to provide unique geneticmaterial for mapping populations for use in functionalgenomics and molecular breeding has not been explored.The results indicated that anther culture is a feasibletechnology that can be used for accelerating rice breedingprogram in Indonesia.